Educating for human dignity : learning about rights and responsibilities - Reardon, Betty (Pennsylvania studies in human rights., 1995)
Issues of universal human rights are critically important topics in education today. Educators, scholars, and activists urge schools to promote awareness and understanding of human rights in their curricula from the earliest levels. Written by Betty A. Reardon, one of the foremost scholars on human rights education for the primary and secondary levels, Educating for Human Dignity is designed for both teachers and teacher educators. It is the first resource offering both guidance and support materials for human rights education programs from kindergarten through high school. It opens possibilities for an holistic approach to human rights education that directly confronts the values issues raised by human rights problems in a context of global interrelationships.